If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + -1(4 + -2x) = 4 10 + (4 * -1 + -2x * -1) = 4 10 + (-4 + 2x) = 4 Combine like terms: 10 + -4 = 6 6 + 2x = 4 Solving 6 + 2x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 2x = 4 + -6 Combine like terms: 6 + -6 = 0 0 + 2x = 4 + -6 2x = 4 + -6 Combine like terms: 4 + -6 = -2 2x = -2 Divide each side by '2'. x = -1 Simplifying x = -1
| 17-n=79 | | 2*5*1.5-1-3= | | 18y+9-28*9y+9=0 | | ln(x+3)+ln(x-3)=5t | | 2*5x-1-3=11 | | 7.3*X=6.8 | | 3(2x-6)=-2(x+2) | | 28=0.001(0.732x^2+15.417x+605.738) | | (-5x^2)+9x+8=0 | | 3*(3/4)^2-(2*3/4) | | -5u-(7/2)=(1/3)u-(4/3) | | -6v-11=5v | | 8(v+1)-4v=2(2v+4)-16 | | -.8t+.4=.66666666667 | | (7+3)/2+3x8 | | 24-1/28(3x)=16-1/28(2x) | | x=4x-(30) | | 8x-5=3x+4.25 | | 68xyz= | | (1/5)(7t-7)=(t+7/10) | | 6=7/(v+6) | | -1v+5+6vx=1+5v+3 | | 7/5+1/7y | | 10.5-0.9Z-1.2-1.2Z=13-2.1Z-7.1 | | 3*(3/4)^2-(2*3/4)/5*(3/4)-1 | | 7=p+13 | | 35x^2y= | | -4/5(z-1/2)=-1/2(z+3) | | 9t-6t+1=0 | | 10.5-0.9Z-1.2=13-2.1Z-7.1 | | 6-z/3=-12 | | 3t+4=-8 |